A radioimmunocytological quantitative method for the rapid detection of ras oncogene p21 protein in mammalian cells. Issue 4 (April 1986) - Spandidos, Demetrios A.; Dimitrov, Todor; Kam, Ephraim Y.
Abstract : In order to provide a sensitive and quantitative detection method of ras p21 at the cytological level, the monoclonal antibody Y 13 259 and iodinated protein A were used to locate the ras protein in various mammalian cell lines. The subsequent autoradiograph can be analysed by a computer-assisted system which showed in these reported experiments that the relative levels of p21 detected in these cells corresponded to results obtained earlier using conventional biochemical methods.